„We wspólnym piekle”. Transnarodowość i nowy sposób prezentowania historii w czeskim kinie na przykładzie Malowanego ptaka Václava Marhoula - Maciejewska, Marta (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The subject of this article is two aspects related to the film The Painted Bird (2019) by Czech director Václav Marhoul: the way history is depicted (in a way that is different from other Czech films after 1989), and the issue of transnationalism (because the film was made in this perspective). Marhoul’s film is set in the context of historical cinema, Czech cinematography after the Second World War and present-day foreign film circulation. Critical reception and interviews with the director are important to me: in order to fully explain how the film is received, and to which works of European art cinema it is compared in order to fully confirm the thesis of its transnationalism. In my article, I cite the theories and features of the concept of transnationalism developed by many other scholars to demonstrate the specificity of The Painted Bird.